2011
DOI: 10.1186/1471-2180-11-19
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal characterization of antimicrobial resistance genes in feces shed from cattle fed different subtherapeutic antibiotics

Abstract: BackgroundEnvironmental transmission of antimicrobial-resistant bacteria and resistance gene determinants originating from livestock is affected by their persistence in agricultural-related matrices. This study investigated the effects of administering subtherapeutic concentrations of antimicrobials to beef cattle on the abundance and persistence of resistance genes within the microbial community of fecal deposits. Cattle (three pens per treatment, 10 steers per pen) were administered chlortetracycline, chlort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 40 publications
6
40
0
Order By: Relevance
“…The phenomenon of different ARGs exhibiting different behaviors is not uncommon in manure or soil systems. Alexander and co-workers used qPCR to monitor the abundance of ARGs in cattle fecal deposits and their results showed that some ARGs (i.e., tet(B), tet(C), sul(I), sul(II), and erm(A)) first increased and then declined, while other ARGs (tet(M) and tet(W)) gradually decreased over 175 days (Alexander et al, 2011). Fig.…”
Section: Antimicrobialmentioning
confidence: 99%
“…The phenomenon of different ARGs exhibiting different behaviors is not uncommon in manure or soil systems. Alexander and co-workers used qPCR to monitor the abundance of ARGs in cattle fecal deposits and their results showed that some ARGs (i.e., tet(B), tet(C), sul(I), sul(II), and erm(A)) first increased and then declined, while other ARGs (tet(M) and tet(W)) gradually decreased over 175 days (Alexander et al, 2011). Fig.…”
Section: Antimicrobialmentioning
confidence: 99%
“…The levels of tet genes were not reduced in faeces of piglets additionally administered oxytetracycline, which was indicated by stable tetA and tetB log 10 gene copy numbers at both time points (d10, d28), compared to declining ones in nonantibiotic treatments. Previous studies reported elevated levels of resistant bacteria or resistance genes under selective pressure, revealing a clear association between antibiotic consumption and antibiotic resistance [31][32][33]. Interestingly, shedding of tetraycline resistant bacteria in faecal samples continued after withdrawal of the antibiotic, indicating a long-lasting effect of antibiotic supplementation.…”
Section: Discussionmentioning
confidence: 92%
“…Most studies on the persistence of antimicrobial-resistant bacteria in livestock waste have focused on large scale management systems including stored manure (Duriez and Topp, 2007) or manure applied to soil (Schmitt et al, 2006) and have used viable bacteria to describe resistance levels. Alexander et al (2011) investigated the persistence of antimicrobial resistance genes sampled in E. coli strains from cattle feces under ambient field conditions and they reported persistence for 175 days. In this study a high degree of resistance to 10 antimicrobial drugs was found among STEC non-O157 strains and also in non-STEC strains, in agreement with the data reported by Mora et al (2005), who verified that there was no difference in the antimicrobial resistance patterns of STEC strains when compared to non-STEC strains.…”
Section: Discussionmentioning
confidence: 99%